ANALISIS ROA DAN DER TERHADAP HARGA SAHAM PADA SUB SEKTOR BUILDING CONSTRUCTION DI BEI: Studi Pada Perusahaan yang Terdaftar di ISSI 2012 -2018 - Ratu Putri Lindasari Hakim; Efi Syarifudin; Mukhlishotul Jannah (Tazkiya, 2019)
Growth trend of building construction sub-sector in 2012 - 2018 More than what is left but still able to survive, more than companies whose share prices continue to rise, then increase growth and development again until 2018 and become a sub-sector that has a good trend now . Return On Assets (ROA) is a profitability ratio that can show all the effectiveness of management in generating profits with available assets. With Debt to Equity Ratio (DER) is a solvency ratio that is able to show the composition of funds provided by investors or borrowers (creditors) with company owners. ROA and DER are considered important in the consideration of investors to buy shares, so a stock price is formed. The purpose of this study is to analyze the use of ROA partially on Stock Prices, DER partially on Stock Prices, ROA and DER simultaneously with respect to Stock Prices. The research method used is quantitative research methods. The analysis technique used is panel regression data, regression model selection, classic assumption test, t test, F test, coefficient of consideration and coefficient of determination. Data analysis techniques using the help of Eviews 9 program. The results of this research analysis are partial ROA which is not significant to the Share Price, obtaining a t-count value smaller than the table value (-2.03452 <0.7080 <2.03452). DER is not significant to the Share Price, based on the value added t count is smaller than the value of the table (-2.03452 <0.5715 <2.03452). Simultaneously ROA and DER have no significant effect on stock prices, based on Fcount <F table (0.234513 <4.14) and the probability of 0.792550 which is greater than 0.05 (0.792550> 0.05).